Transcriptional Time Course After Rotator Cuff Tear - Vasquez-Bolanos, Laura S.; Gibbons, Michael C.; Ruoss, Severin; Wu, Isabella T.; Vargas-Vila, Mario; Hyman, Sydnee A.; Esparza, Mary C.; Fithian, Donald C.; Lane, John G.; Singh, Anshuman; Nasamran, Chanond A.; Fisch, Kathleen M.; et al. (Frontiers in Physiology, 2021)
Rotator cuff (RC) tears are prevalent in the population above the age of 60. The disease progression leads to muscle atrophy, fibrosis, and fatty infiltration in the chronic state, which is not improved with intervention or surgical repair. This highlights the need to better understand the underlying dysfunction in muscle after RC tendon tear. Contemporary studies aimed at understanding muscle pathobiology after RC tear have considered transcriptional data in mice, rats and sheep models at 2–3 time points (1 to 16 weeks post injury). However, none of these studies observed a transition or resurgence of gene expression after the initial acute time points. In this study, we collected rabbit supraspinatus muscle tissue with high temporal resolution (1, 2, 4, 8, and 16 weeks) post-tenotomy (n = 6/group), to determine if unique, time-dependent transcriptional changes occur. RNA sequencing and analyses were performed to identify a transcriptional timeline of RC muscle changes and related morphological sequelae. At 1-week post-tenotomy, the greatest number of differentially expressed genes was observed (1,069 up/873 down) which decreases through 2 (170/133), 4 (86/41), and 8 weeks (16/18), followed by a resurgence and transition of expression at 16 weeks (1,421/293), a behavior which previously has not been captured or reported. Broadly, 1-week post-tenotomy is an acute time point with expected immune system responses, catabolism, and changes in energy metabolism, which continues into 2 weeks with less intensity and greater contribution from mitochondrial effects. Expression shifts at 4 weeks post-tenotomy to fatty acid oxidation, lipolysis, and general upregulation of adipogenesis related genes. The effects of previous weeks’ transcriptional dysfunction present themselves at 8 weeks post-tenotomy with enriched DNA damage binding, aggresome activity, extracellular matrix-receptor changes, and significant expression of genes known to induce apoptosis. At 16 weeks post-tenotomy, there is a range of enriched pathways including extracellular matrix constituent binding, mitophagy, neuronal activity, immune response, and more, highlighting the chaotic nature of this time point and possibility of a chronic classification. Transcriptional activity correlated significantly with histological changes and were enriched for biologically relevant pathways such as lipid metabolism. These data provide platform for understanding the biological mechanisms of chronic muscle degeneration after RC tears.